Ultrathin flexible electrospun EVA nanofiber composite with electrothermally-driven shape memory effect for electromagnetic interference shielding - Wei, Wanting; Zhang, Pengfei; Cao, Feng; Liu, Junhao; Qian, Kun; Pan, Diankun; Yao, Yongtao; Li, Wenbing (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •Electrothermally-driven shape memory EVA@PDA@Ag fiber membranes are prepared.•High electrical conductivity of 2.5 × 105 S/m and EMI SE of 87 dB are achieved.•The superb EMI SE can be maintained after cyclic folding and ultrasound.•The shape can be programmed and recovered at 0.55 V or 80 °C.•The membrane gives an intelligent way for FPC electromagnetic shielding film. When a 5G folding mobile phone is in a complex electromagnetic environment, it will unavoidably be subject to electromagnetic interference with a frequency of 450 MHz–6 GHz from electronic components on internal and external flexible printed circuits (FPCs). Here, we propose a method to prepare ultrathin, flexible and conductive polymer fiber composite (CPFC) with excellent shape memory effect and superb electromagnetic interference shielding effectiveness (EMI SE). The shape-memorized CPFC (SMCPFC) can be fabricated by three steps: (1) preparing highly cross-linked ethylene–vinyl acetate copolymer (EVA) fiber membrane by electrospinning and UV cross-linking; (2) synthesizing a polydopamine (PDA) layer on mat surface; (3) promoting the reduction of Ag nanoparticles on EVA@PDA fibrous composite surface. The electrical conductivity of SMCPFC can reach up to 2.5 × 105 S/m, and its average EMI SE is close to 90 dB at the frequency of 3.94–5.99 GHz. After cyclic stretching, folding, and ultrasonic washing, the conductivity and EMI SE maintains unchanged. In addition, SMCPFC has an outstanding electrothermally-driven shape memory effect. Shape can be programmed immediately at 0.55 V, and 50% strain sample exhibits EMI SE of 50.91 dB, which can blocks more than 99.99% electromagnetic waves. Shape can be recovered at 80 °C, EMI SE of recovery sample is roughly the same as that of the original sample (87.06 dB), and 99.9999997% electromagnetic waves can be consumed. The invention of this multifunctional SMCPFC gives a new way for FPC electromagnetic shielding film to develop towards the directions of intelligence and multi-functions.